Neck transection level and postoperative pancreatic fistula after pancreaticoduodenectomy: A retrospective cohort study of 195 patients. (October 2020) - Bardol, Thomas; Delicque, Julien; Hermida, Margaux; Herrero, Astrid; Guiu, Boris; Fabre, Jean-Michel; Souche, Regis
Abstract: Background: The aim of this study was to evaluate the impact of the level of neck transection on clinically relevant postoperative pancreatic fistula (CR-POPF) after standard pancreaticoduodenectomy (PD) with pancreaticojejunostomy. Method: A total of 195 patients with an early postoperative CT scan were retrospectively analyzed and divided into 2 groups (CR-POPF and No CR-POPF) in order to seek potential risk factors for CR-POPF. We focused our analysis on the relationship between CR-POPF and the level of neck transection, defined by measuring the distance between the left side of the portal vein and the remnant pancreatic stump on the postoperative CT scan. Result: CR-POPF occurred in 58 out of 195 PD (29.7%); grade B (17%) and grade C (12.7%). The Clavien-Dindo ≥ 3 morbidity rate was 33% (65/195) and the mortality rate was 2.5% (5/195). Multivariate analysis indicated that a 'right-sided' level of neck transection ( P = 0.007), a firm pancreatic texture ( P = 0.001), and a PD for non-pancreatic ductal adenocarcinoma histology ( P = 0.032) were independent risk factors for CR-POPF. A full neck resection with systematic transection ≥7 mm at the left side of the portal vein seems to prevent CR-POPF harboring a protective effect (OR 0.056; 95% CI 0.003 to 0.978; P = 0.039). Conclusion: Here we further consolidate the concept describing the pancreatic neck as a vascular watershed, showing that a long remnant pancreatic neck could be an independent risk factor for CR-POPF after PD (NCT03850236). Trial registration number and agency: The present study was approved by our local ethics committee and was declared on ClinicalTrials.gov (ID: NCT03850236). Highlights: The pancreatic neck is described as a zone lacking proper vascularization. We focused on the level of neck transection in 195 pancreaticoduodenectomies. A long remnant neck was an independent risk factor for pancreatic fistula (PF). A soft pancreatic texture and benign lesions were independent risk factors for PF. A full neck resection by shifting transection 'to the left' seems to prevent PF.